ISSUES OF THE DEVELOPMENT OF CONNECTED SPEECH IN CHILDREN 5-7 YEARS OLD WITH A DIFFERENTIATED APPROACH TO LEARNING - Gulnoza Odilovna Najmiddinova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this article, the pedagogical problem of the development of coherent speech of preschoolers 5-7 years old with a differentiated approach to learning. The essence of the concept is revealed: "a differentiated approach in preschool education". Some ways of solving this problem are proposed.